To find the solution of both equations, we can solve the system of equations simultaneously.
First, let's rewrite the given equations:
1) X - 5Y = 7
2) 3X - 2Y = -4
To solve this system, we can use elimination or substitution method. Let's use the elimination method:
First, we need to manipulate the equations to make the coefficients of X or Y the same in both equations. Let's multiply the first equation by 3 and the second equation by 1 to have the coefficient of X be the same.
3) 3(X - 5Y) = 3(7) --> 3X - 15Y = 21
4) 1(3X - 2Y) = 1(-4) --> 3X - 2Y = -4
Now we can subtract equation 4 from equation 3:
3X - 15Y - (3X - 2Y) = 21 - (-4)
3X - 15Y - 3X + 2Y = 21 + 4
-13Y = 25
Y = -25/13
Now that we have found the value of Y, we can substitute it back into one of the equations to solve for X. Let's substitute into equation 1:
X - 5(-25/13) = 7
X + 125/13 = 7
X = 7 - 125/13
X = 91/13 - 125/13
X = -34/13
Therefore, the solution to the system of equations X - 5Y = 7 and 3X - 2Y = -4 is X = -34/13 and Y = -25/13.
3X minus 2Y equals -4
X minus 5Y equals three
Review the graph of a system of two linear equations into variables X minus 5Y equals seven and 3X minus 2Y equals -4 find the solution of of both equations
1 answer